2014
DOI: 10.1208/s12248-014-9654-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Size, and Solubility of Antigen Arrays Determines Efficacy in Experimental Autoimmune Encephalomyelitis

Abstract: ABSTRACT. Presentation of antigen with immune stimulating "signal" has been a cornerstone of vaccine design for decades. Here, the antigen plus immune "signal" of vaccines is modified to produce antigen-specific immunotherapies (antigen-SITs) that can potentially reprogram the immune response toward tolerance of an autoantigen. The codelivery of antigen with a cell adhesion inhibitor using Soluble Antigen Arrays (SAgAs) was previously shown to slow or halt experimental autoimmune encephalomyelitis (EAE), a mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 60 publications
(94 reference statements)
0
36
0
Order By: Relevance
“…cSAgA PLP showed enhanced efficacy when compared to SAgA PLP , possibly due the more stable covalent linkage in cSAgA PLP . 7,[17][18][19][20][21][22][23] While the immune response of MS is distinct from T1D, the mechanism of SAgAs offers a general strategy for the delivery of autoantigens. Here, we tailored SAgA technology as an ASIT for T1D.…”
Section: Introductionmentioning
confidence: 99%
“…cSAgA PLP showed enhanced efficacy when compared to SAgA PLP , possibly due the more stable covalent linkage in cSAgA PLP . 7,[17][18][19][20][21][22][23] While the immune response of MS is distinct from T1D, the mechanism of SAgAs offers a general strategy for the delivery of autoantigens. Here, we tailored SAgA technology as an ASIT for T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers around the world have reported the biomimetic micro-and nanoparticles (MNPs) carrying myelin peptides or proteins along with toxin or regulatory molecules for the treatment of EAE or MS (30,40,41). s.c. prophylactic and therapeutic vaccination with PLGA NPs encapsulating MOG 35-55 peptide and IL-10 ameliorated the MOG-induced EAE in mice (42).…”
Section: Discussionmentioning
confidence: 99%
“…To fabricate the multivalent TaAPCs, PLGA-MPs TGF-b1 were further cocoupled with the target Ags (MOG 40 TaAPCs) were generated in parallel and followed by threecolor staining. The histograms (Fig.…”
Section: Generation and Characterization Of Plga Mps And Multivalent mentioning
confidence: 99%
“…They showed that the administration of NP-loaded DC could induce immune tolerance in CD4 þ T-cells and inhibit EAE progression. Similarly, Sestak et al (2014) reported how the physical characteristics of the carrier such as structure, size and solubility can modulate the immune response following treating EAE. They evaluated a bifunctional peptide (small and soluble), Soluble Antigen Arrays (SAgAs) (large and soluble) and PLGA NP (large and insoluble) all exhibiting PLP and intercellular cell adhesion molecule-1 ligand derived from aL-integrin (CD11a 237-246 ).…”
Section: Treatmentmentioning
confidence: 99%